ANALYSIS REGARDING THE IMPORTANCE OF PROMOTION IN STEEL COMPANIES IN INDONESIA - Yapari, Reinaldi (Universitas Ciputra, 2020)
The purpose of this research is to find out the promotion and marketing strategy for steel companies in Indonesia. The research method used in this research is qualitative and quantitative research methods. Qualitative research methods include interviews with resource persons and product users (extreme users and expert users) as well as literature studies of journals related to light steel, promotion, and marketing strategy. The conclusion of this research is the need for a promotion that can be accepted by customers and to be able to promote steel companies in Indonesia. Keyword: branding, marketing, promotion, customers, steel